Pengembangan media edukasi diabetes mellitus untuk tenaga kefarmasian di puskesmas wilayah Mataram - Ni Made Amelia Ratnata Dewi; Iman Surya Pratama; Candra Dwipayana Hamdin (INDRA: Jurnal Pengabdian kepada Masyarakat, 2021)
Adherence in using drugs is one of the factors that determine the success of therapy, especially for chronic diseases such as diabetes mellitus. Efforts that can be made by health workers in increasing adherence to diabetes mellitus sufferers in undergoing treatment are to pay attention to providing information and education to patients. The purpose of this community service activity is to develop educational media for type II diabetes mellitus for pharmaceutical workers in the Mataram regional health center. Making diabetes education media is done by making a pocket book which aims to make it easier for health workers to carry out counseling related to diabetes mellitus and its treatment.